The incoherence of human rights in international law : absence, emergence, and limitations - Ashley, Louisa; Butler, Nicolette (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2025)
"Incoherence is a term that is all too often associated with the public international law regime. To a great extent, its incoherence is arguably a natural consequence of the fragmented nature of both the development and overall scope of the discipline. Despite significant achievements since the Universal Declaration of Human Rights (1948), a coherent human rights regime that is properly integrated with other branches of public international law is still lacking. This book explores this incoherent approach to human rights, including specific challenges that arise as a result of the creation and regulation of legal relationships between parties (state and non-state) that sit outside of the human rights framework, with a view to considering how it may be remedied. Divided into three parts, the collection provides a critical exploration of various challenges and barriers related to the absence of human rights in some instances, contemporary emergence of rights, and a lack of rights fulfilment in others. These three situations are considered within the wider context of, and difficulties facing, a human rights-based approach to international law. Each of the three parts aligns with one of the three prime responsibilities and duties of states in respect of international human rights: to promote, to protect and to fulfil. The contributions represent different perspectives in international law and human rights and how the global agenda of promoting human rights, the rules-based international order, and multilateralism requires further strengthening - the lens of incoherence providing a means to understand particular inconsistencies. Chapters focus upon subjects including international investment law, international financial contracts, the arms trade, indigenous peoples' rights, rights of peasants, the right to a clean, healthy and sustainable environment, the right to food, and transitional justice. Presenting a critical exploration of key contemporary challenges and the implementation of human rights law in different contexts, the collection will be of interest to a wide-ranging audience of international law and international relations scholars and practitioners, and students of law, politics and globalisation across the world"--
'Human Rights Deficit in Sovereign Loan Contracts' / Ilias Bantekas -- 'The Basis for Indigenous Peoples' Rights in International Investment Agreements' / Okechukwu Ejims -- 'Economic Sanctions in Conflict with Human Rights' / Joy Gordon -- 'Debating International Intellectual Property : A TWAIL Perspective' / Pratyush Nath Upreti -- 'The Arms Trade and Responsibility for Human Rights : The Blind Spot in International Human Rights Law' / Abdulmalik Altamimi -- 'Protecting Human Rights through International Trade Agreements : The Case of Labour Standards' / Joanna Gomula -- 'The Emerging Human Right to a Clean Environment and its Limitations' / Malgosia Fitzmaurice -- 'The Emergence of Posthuman Legalities and Peasant Rights' / Louisa Ashley -- 'State's "Agency" Over Algorithmic Decision-Making : the Role of the Regulator' / Abhinayan Basu Bal and Trisha Rajput -- 'Cambodia and the Progressivist "Imaginary" : the Limitations of International(-ised) Criminal Tribunals as Mechanisms for Implementing Human Rights' / Alex Batesmith -- 'The Right to Food : A United Kingdom Perspective' / Michael Cardwell and Clare James -- 'Integrating Human Rights into Investment Treaties : The EU Approach' / Nicolette Butler and Niyoosha Shishehgar -- 'The Fulfilment of Human Rights in Times of Transition : Towards Coherence in Post-Cold War ECtHR Cases' / James Sweeney.
Keywords: International law and human rights; LAW / Civil Rights; POLITICAL SCIENCE / Political Freedom & Security / Civil Rights; LAW / International